2007
DOI: 10.1007/s00244-006-0042-2
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Nonylphenol and Octylphenol on Embryonic Development of Sea Urchin (Paracentrotus lividus)

Abstract: In this study, embryotoxic and genotoxic effects of nonylphenol (NP) and octylphenol (OP), which are the derivates of alkylphenol (APs), were evaluated using the gametes and embryos of the sea urchin Paracentrotus lividus. The sperm and eggs of sea urchins were exposed to increasing concentrations of NP (0.937-18.74 microg/L) and OP (5-160 microg/L) under static conditions. The endpoints were sperm fertilization success, quantitative and morphologic changes in mitotic activity, larval malformations, developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Many studies reported a negative effects of different pollutants on spermatozoa of marine organisms (Abascal et al, 2007;Au et al, 2000;Boni et al, 2016;Rurangwa et al, 2002); however, the effects of NPs have been poorly elucidated (Châtel et al, 2017;Gallo et al, 2016;Kadar et al, 2011). In ecotoxicological studies, fertilization success are commonly used as endpoint to evaluate the effects of sperm exposure to NPs (Arslan et al, 2007;Dinnel et al, 1989;Mwatibo and Green, 1997;Vaschenko et al, 1999;Volpi Ghirardini and Arizzi Novelli, 2001;Warnau et al, 1996). Even though NPs are known to induce various cellular defects in spermatozoa affecting fertilization success, ecotoxicological investigations rarely use cellular biomarkers to test spermiotoxicity of NPs (Kadar et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Many studies reported a negative effects of different pollutants on spermatozoa of marine organisms (Abascal et al, 2007;Au et al, 2000;Boni et al, 2016;Rurangwa et al, 2002); however, the effects of NPs have been poorly elucidated (Châtel et al, 2017;Gallo et al, 2016;Kadar et al, 2011). In ecotoxicological studies, fertilization success are commonly used as endpoint to evaluate the effects of sperm exposure to NPs (Arslan et al, 2007;Dinnel et al, 1989;Mwatibo and Green, 1997;Vaschenko et al, 1999;Volpi Ghirardini and Arizzi Novelli, 2001;Warnau et al, 1996). Even though NPs are known to induce various cellular defects in spermatozoa affecting fertilization success, ecotoxicological investigations rarely use cellular biomarkers to test spermiotoxicity of NPs (Kadar et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Concerning studies on aquatic snails, Oliveira-Filho et al [40] found a LC50 for Biomphalaria tenagophila embryos between 29.25 and 640.25 mg/l following exposure duration and Lalah et al [41] showed that the branched NP isomer (4(3 ,6 -dimethyl-3 -heptyl)-phenol at an average concentration of 0.105 mg/l) slowed the embryonic growth and reduce hatching success of L. Stagnalis; both authors suspected that this low observed effect on embryos is probably due to a reduced penetration of NP in the lengthwise encapsulating jelly strand that surrounds the eggs [40,41]. NP also induces concentration-dependent malformations of sea urchin embryos [42] and these authors find, as we do, that embryos are blocked at early stage.…”
Section: Disruption Of Embryogenesismentioning
confidence: 95%
“…At present, only a few studies have examined the toxicity of EDCs to embryos of invertebrate species using benthic diatoms as the settlement substrate (Liu et al 2009). Arslan et al (2007) investigated the acute toxicity of NPs to the embryonic development of the sea urchin Paracentrotus lividus and found that the effective concentration was within an environmentally relevant range, from 0.937 to 18.74 lg L -1 , but the contribution from benthic diatoms was not mentioned.…”
Section: Introductionmentioning
confidence: 98%